Eco-Spiritual Resilience: Designing Quality Islamic Education to Age of Screen Overload - Arini Nuora Darina; Hasan Baharun (Al-Qalam Institute, 2025)
Formulating a quality Islamic education model through an eco-spiritual approach to address the challenges of the digital era, characterized by the high intensity of layer use, is the purpose of this study. This study aims to answer the question of how Islamic education can shape individuals who have spiritual resilience and ecological awareness in facing the challenges of the digital world. The research method is a qualitative approach, using data collection techniques such as literature reviews, interviews, and observations of the implementation of Islamic education across various educational institutions. The results of the study show that Islamic education grounded in eco-spiritual resilience has great potential to help individuals overcome the negative impacts of technology, such as cell phone addiction, reduced quality of social relationships, and spiritual crises. The concept of eco-spiritual resilience, integrating Islamic values that prioritize the balance between the physical and the digital and maintain harmony with nature, is part of a comprehensive education. The findings of this study call for the development of Islamic education that not only focuses on improving students' thinking skills, knowledge, and morals, but also on strengthening their psychological and spiritual resilience. Thus, students are expected to respond to technological pressure wisely by maintaining balance in their daily lives.